Seroprevalence and trends of markers of transfusion transmissible infections among blood donors: a 3-year hospital based-study - Alcantara, Jerold C.; Alenezi, Farhan Khalaf M.; Haj Ali, Omar Hafiz (International Journal Of Community Medicine And Public Health, 2018)
Background: Evaluating the trends and rates of transfusion-transmitted infections (TTIs) among blood donors ensure that supplies of blood are safe and a proficient donor screening is in place. Hence, the study assessed the prevalence and trends of TTI markers among blood donors in Hail, Saudi Arabia. Methods: A retrospective review was done using donor records in a 3-year period from January 2013 to December 2015. All samples underwent to mandatory serological screening. Descriptive and inferential statistics were used appropriately. Distribution tables were developed to discern the trends that exist and compare the prevalence rates among different age groups. Significant level was set at 5% (p<0.05). Results: Of the 11,162 blood donors evaluated, 1.5% was found positive for TTI markers. The overall prevalence of HBV, HCV, HTLV I/II, syphilis and malaria were 1.2, 0.04, 0.07, 0.2 and 0.02%, respectively. No blood donor showed positive for HIV markers. Majority of the infections were evident among replacement donors (57.3%). Greater number was observed from the age group of 30-39 years. Statistically, there was no significant difference among the various age groups. Conclusions: The prevalence rate of TTIs in this study is comparably lower than in other regions of Saudi Arabia and some countries, with no significant variation among the different age groups. HBV continues to be the highest rate of infections inflicting blood donors. Methods to improve donor retention, encouragement and recruitment of new donors have to be identified.